Physical match demands across different playing positions during transitional play and high-pressure activities in elite soccer - Bortnik, L.; Bruce-Low, S.; Burger, J.; Alexander, J.; Harper, D.; Morgans, R.; Carling, C.; McDaid, K.; Rhodes, D. (Biology of Sport, 2024)
This study explored physical match demands across different playing positions during transitional play, to inform the need for position-specific training interventions. Data was collected using 10 Hz GPS units from 10 competitive matches including 23 elite soccer players of the 1st Polish Division (Ekstraklasa) in season 2020-21. A total of 4249 positional observations were made; center backs (n = 884), full backs (n = 972), central defensive midfielders (n = 236), central attacking midfielders (n = 270), central midfielders (n = 578), wingers (n = 778), and attackers (n = 531). Match data reflected distances covered per minute (m·min-1): total distance (TD), high-speed running distance (HSRD, > 19.8 km·h-1), sprint distance (SD, > 25.2 km·h-1), and the frequency of high-intensity accelerations and decelerations (A+D, > 3 m·s -2; n·min-1). Total absolute sprint distance (SD, > 25.2 km·h-1) and total relative sprint distance (Rel B5) were also quantified. A univariate analysis of variance revealed position-specific differences. Significant effects of position were found for all analysed metrics during transitional play (large ESs; p < .001). Central attacking midfielders displayed higher TD (m·min-1), fullbacks covered highest SD (m·min-1) and wingers achieved the highest A+D (n ·min-1) (p = 0.05). Centre backs displayed the lowest physical outputs when compared to all other positions, except in A+D (n ·min-1) during defensive transitions (p = 0.05). Attackers displayed the highest physical metrics during high pressure activities (p = 0.05). Coaches should carefully consider positional transitional demands to better inform training design. With specific attention paid to drills that replicate game play.